Preserving archives - Forde, Helen (London Facet Pub., 2007)
"Access to archival material - the documentary heritage of people all over the world that gives them their identity and ensures their rights - is dependent on the survival of fragile materials: paper, parchment, photographic materials, audiovisual materials and, most recently, magnetic and optical formats. The primary importance of such survival is widely acknowledged but sometimes overlooked in a rush to provide ever better means of access. But without the basic material, no services can be offered. Preservation is the heart of archival activity. Archivists in all types of organizations face questions of how to plan a preservation strategy in less than perfect circumstances, or deal with a sudden emergency. This book considers the causes of threats to the basic material, outlines the preservation options available and offers flexible solutions applicable in a variety of situations. Benefiting from the author's contact with international specialists as Head of Preservation Services at the National Archives of the UK, it offers a wide range of case studies and examples."--Back cover.
Introducing archive preservation -- Understanding archive materials and their characteristics -- Managing digital preservation -- Archive buildings and their characteristics -- Safeguarding the building and its contents -- Managing archival storage -- Managing risks and avoiding disaster -- Setting up a conservation workshop -- Moving the records -- Exhibiting archives -- Handling the records -- Managing a pest control programme -- Using and creating surrogates -- Putting preservation into practice.
Keywords: Archival materials -- Conservation and restoration